Agrobacterium rhizogenes-mediated hairy roots transformation as a tool for exploring aluminum-responsive genes function. (8th February 2019) - Daspute, Abhijit A; Yunxuan, Xian; Gu, Minghua; Kobayashi, Yuriko; Wagh, Sopan; Panche, Archana; Koyama, Hiroyuki
Aim: To develop a useful alternative approach to evaluate the gene function in hairy roots.Methods: Arabidopsis and tobacco (wild-type or mutant) were a host for Agrobacterium rhizogenes transformation.Results: The hairy roots formation efficiency ranged from 53 to 98% in tobacco and 53 to 66% in Arabidopsis . Hairy and intact roots showed similar gene expression pattern in response to salt and aluminum stress. Genomic polymerase chain reaction and fluorescent images showed high rate (>80%) of co-integration of T-DNAs and uniform cell transformation without use of any antibiotic selection. Whole processes of hairy roots were completed within 1 month after the infection of Agrobacterium .Conclusion: Aluminum-responsive orthologous gene function could be evaluated by NtSTOP1- KD and Atstop1 as a host for hairy roots transformation. Lay abstract: Hairy roots have been used for various purposes over the last several years. In the present study we used Agrobacterium rhizogenes -mediated hairy roots as an alternative approach for Agrobacterium tumefaciens transformation. We developed a simple, effective and reproducible hairy root protocol in tobacco and Arabidopsis . Developed hairy roots were compared with intact roots to characterize the gene response to aluminum, NaCl stress and cellular localization of genes. Aluminum-responsive orthologous genes function could be evaluated by using NtSTOP1- KD and Atstop1 as a host for hairy roots transformation.